PROBLEMS OF FORMATION ANTICORRUPTION LEGAL AWARENESS - A, Joshua Castellino; K., Mynbatyrova N. (Farabi Journal of Social Sciences, 2019)
Abctract. The article is consider problem of current corruption and how to deal with it is discussed. At the same time, modern peculiarities of the legal awareness of anti-corruption law are analyzed and studied. The author of the article also pays special attention to the development of legal awareness. The results and conclusions reached by the author can be used to ensure the state policy, increase the legal awareness of the society, and encourage the legal education of the society. Corruption in all its manifestations represents a serious threat to the national security of any state, has a destabilizing effect on all areas of society and the individual. The key to successfully countering its manifestations is not only the effective operation of state institutions in this area, but also a clear understanding by every citizen of corruption as an absolutely unacceptable social phenomenon. Corruption is a large-scale problem of our time. No state, regardless of its socio-economic and political structure, has absolute immunity to corruption. Today we are talking about the fight against corruption, its development and structure, the world outlook of citizens, and the whole economy. The First President of the Republic of Kazakhstan, the Leader of the Nation Nazarbayev N.A. underlined in his annual Address to the people of Kazakhstan the importance of anti-corruption. Anti-corruption has become one of the priority directions of Kazakhstan's legal reform. At this point, corruption issues are frequently heard in the media and public speeches. Different ways and methods of combating corruption are being developed.